CRISPR-Cas9 Genome Editing Technology: Development and Applications - Soni, Anjali; Shaikh, Hala (IJRDO-Journal of Applied Science, 2016)
The discovery of an ancient adaptiveimmune system in bacteria, called the CRISPR/Cassystem, has revolutionalized the modern science. Thebacterial proteins that identify and target viral DNAfor degradation have been characterized andmanipulated for a variety of uses in agriculture,molecular biology and medicine. Clustered RegularlyInterspaced Short Palindromic Repeats(CRISPR)/CRISPR-associated (Cas) protein 9 systemprovides a robust and multiplex genome editing tool,enabling researchers to precisely manipulate specificgenomic elements and facilitating the elucidation oftarget gene function in biology and diseases.CRISPR-Cas9 gene editing technique has set thestage for remarkable developments. This technologyis used to modify, regulate, or mark genomic loci in awide variety of cells and organisms from all threedomains of life. These results highlight a new era inwhich genomic manipulation is no longer abottleneck to experiments, paving the way towardfundamental discoveries in biology, with applicationsin all branches of biotechnology, as well as strategiesfor human therapeutics.